Variceal Bleeding a Predictor of Mortality in Patient Admitted with Liver Cirrhosis - Shah, Syed Nadir; Moneeb Ur Rehman; Khan, Hasil; Mansoor, Javeria; Fazal ur Rehman; Manzoor, Rida; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
This study aims to assess the risk of mortality in cirrhotic patients with acute variceal bleeding at a tertiary care hospital. Variceal bleeding is a common and life-threatening complication in liver cirrhosis, significantly contributing to early mortality. The study utilized a cohort design with 128 patients, divided into two groups: those with acute variceal bleeding (exposed) and those without (unexposed). Baseline clinical data, including Child-Pugh and MELD scores, were collected. The primary outcome was 30-day mortality. Key findings include a mean age of 55.7 ± 22.1 years, with 52.8% males and 56.3% from rural areas. The average Child-Pugh score was 10.1 ± 3.2, and the mean MELD score was 24.1 ± 10.1. The frequency of hematemesis and melena as presenting complaints was evenly split at 50%. Mortality was observed in 49.2% of the patients with variceal bleeding. Statistical analysis using chi-square tests revealed a significant association between variceal bleeding and increased mortality (p < 0.05). Confounding factors such as age, gender, and comorbid conditions were controlled through stratification, with relative risk calculations confirming the elevated mortality risk. This study highlights the critical need for timely interventions in cirrhotic patients with variceal bleeding and underscores the importance of comprehensive management strategies to reduce mortality in this high-risk population.